Cultural prerequisites for the formation of attitudes towards freedom of choice in the accounting system - V.V. Travin; I.A. Nahilenko (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The development of modern society is based on values. They determine the trajectory of development. Therefore, an important task is to determine the list of values that have played a dominant role in the development of Ukrainian society and the formation of Ukrainian identity, and the ability to implement them by a personality, in particular, when making choices and keeping accounting records. The value system of modern Ukrainian society was formed under the influence of European and Byzantine-Eurasian values. The Ukrainian perceives the surrounding world through his own feelings, interprets through the mind, unites them into a single entity, and when they become the basis of his personality, he realizes it through his own will. For such a national character, a personality will always be of great importance, the truth will be realized through a person and will always be of practical importance, and will never appear in the form of a general idea capable of devaluing a person’s life. That is, the Ukrainian identity has a reason for the development of professional responsibility for the choice. In this context, accounting should be considered as a risky professional activity that presupposes the possibility of choice and responsibility for it. Similarly to entrepreneurial skills, accounting abilities, including the ability to take risk and responsibility, should be considered. Awareness of these ideas is possible only under the condition of the mental identification of the subject of accounting within the social and cultural space-time of Ukraine. The ability to understand and use their own identity and values can form an idea of freedom of choice and responsibility.